Thanks to the animals - Sockabasin, Allen, 1944- (Gardiner, Me. : Tilbury House, 2005)
In 1900 during the Passamaquoddy winter migration in Maine, Baby Zoo Sap falls off the family bobsled and the forest animals hearing his cries, gather to protect him until his father returns to find him.
Accelerated Reader AR
Maine author. Allen Sockabasin is Passamaquoddy. Rebekah Raye lives in Blue Hill, Me.
Keywords: Forest animals -- Juvenile fiction; Passamaquoddy Indians -- Juvenile fiction; Babies -- Fiction; Forest animals -- Fiction; Passamaquoddy Indians -- Fiction; Indians of North America -- Maine -- Fiction; Maine -- History -- 20th century -- Fiction